Regolith as raw material for the production of aggregates and concrete-like composites on the Moon - Jacek Katzer; Janusz Kobaka (Archives of Civil Engineering, 2024)
The presented research program is focused on harnessing lunar regolith as raw material for the production of aggregates and concrete-like composites on the Moon. The proposed complex technological solution covers technology of lunar aggregate production, lunar concrete-like composites, shape of a lunar habitat, a type of its structure and erection technique. Each element of the proposed solution is supported by tests or calculations. In authors’ opinion magnetic separation seems to be the most promising technology of lunar aggregate production, habitats should be in egg-shaped form and the structure should be 3D printed as a Voronoi mesh. The research program was conducted using scientifically proven lunar soil simulants which were thoroughly tested by the authors. Production of lunar aggregate and subsequently concrete-like composite based on it is inevitable. The authors’ proposed approach to the erection of lunar habitats is fully based on in-situ resource utilization philosophy increasing its feasibility. Necessary future research areas were pointed out.